A quest\~ao da desigualdade no Brasil: Como estamos, como a populaç\~ao pensa e o que precisamos fazer - Pedro Cavalcante (Instituto de Pesquisa Econômica Aplicada (IPEA), 2020)
– There is a consensus that income inequality is one of the main problems faced by the public administration. Thus, this article develops an innovative analysis of Brazilian citizens' opinions, based on the results of the Oxfam Brasil and Datafolha surveys of 2017 and 2019, about inequalities, comparing convergences and divergences between these views with specialized scientific knowledge. Results showed alignment between citizens' opinion and the field of study, in terms of concepts and diagnosis, the perspective of multi-causality, and the alternatives of public policies to deal with the problem. However, the ordering of these factors varies with the population's income groups. In other words, while the poorest prefer public policies and investments in sectors with immediate effects on their daily lives, the richest are prone to solutions without direct costs to them. In general, the population defends the progressive tax policy, i.e., the wealthiest paying higher tributes. However, they tend to exclude themselves from this population segment, in a logic that 'the rich are the others', although the statistics demonstrate the contrary. In conclusion, the paper brings new reflections to advance the understanding of this complex and dynamic phenomenon and qualify the debate on the limits and possibilities of the public administration's initiatives.
Keywords: H83; 330; public administration; income inequality; public policy; State; Brazil